2017
DOI: 10.1128/jvi.00130-17
|View full text |Cite
|
Sign up to set email alerts
|

Broadening CD4+and CD8+T Cell Responses against Hepatitis C Virus by Vaccination with NS3 Overlapping Peptide Panels in Cross-Priming Liposomes

Abstract: Despite the introduction of effective drugs to treat patients with chronic hepatitis C virus (HCV) infection, a vaccine would be the only means to substantially reduce the worldwide disease burden. An incomplete understanding of how HCV interacts with its human host and evades immune surveillance has hampered vaccine development. It is generally accepted that in infected individuals, a narrow repertoire of exhausted T cells is a hallmark of persistent infection, whereas broad, vigorous CD4 ϩ and CD8 ϩ T cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…This approach was used to elucidate the induction of CD4 + and CD8 + T-cell responses following immunization with recombinant NS3 protein antigen or the corresponding peptide mix both adjuvanted with CAF09. 92 The epitope mapping revealed that immunization with the peptide mix resulted in recognition of more CD4 epitopes compared with the recombinant protein, whereas 2 CD8 epitopes were induced by the peptide mix, while none were observed with the NS3 protein. 92 Pentamer/tetramer/dextramer-conjugated CD8 epitopeloaded MHC-I molecules are used to assess the level of antigenspecific CD8 + T cells in the relevant organs using flow cytometry.…”
Section: Evaluation Of Antibody Responsesmentioning
confidence: 96%
See 2 more Smart Citations
“…This approach was used to elucidate the induction of CD4 + and CD8 + T-cell responses following immunization with recombinant NS3 protein antigen or the corresponding peptide mix both adjuvanted with CAF09. 92 The epitope mapping revealed that immunization with the peptide mix resulted in recognition of more CD4 epitopes compared with the recombinant protein, whereas 2 CD8 epitopes were induced by the peptide mix, while none were observed with the NS3 protein. 92 Pentamer/tetramer/dextramer-conjugated CD8 epitopeloaded MHC-I molecules are used to assess the level of antigenspecific CD8 + T cells in the relevant organs using flow cytometry.…”
Section: Evaluation Of Antibody Responsesmentioning
confidence: 96%
“…92 The epitope mapping revealed that immunization with the peptide mix resulted in recognition of more CD4 epitopes compared with the recombinant protein, whereas 2 CD8 epitopes were induced by the peptide mix, while none were observed with the NS3 protein. 92 Pentamer/tetramer/dextramer-conjugated CD8 epitopeloaded MHC-I molecules are used to assess the level of antigenspecific CD8 + T cells in the relevant organs using flow cytometry. In a DC-based vaccine pulsed with the antigen TRP2 and adjuvanted with soluble poly(I:C), the percentage of TRP2specific CD8 + T cells was assessed using a K b /TRP2 tetramer and an anti-CD8 antibody.…”
Section: Evaluation Of Antibody Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…Again, the adjuvant helped to exceed the immunostimulatory activity of alum adjuvant, increasing antibody and IFN-γ levels, and polarizing the immune response to Th1 type [ 163 ]. A vaccine, based on a mixture of 62 overlapping 20-mer peptides covering HCV NS3 and CAF09 adjuvant, induced polyfunctional T-cell responses in CB6F1 mice [ 164 ]. CAF09 consists of cationic liposomes combined with the immunostimulants monomycolyl glycerol and the TLR3 ligand poly (I:C) [ 171 ].…”
Section: Adjuvants In Hcv Vaccinesmentioning
confidence: 99%
“…An increased breadth of the vaccine-induced T cell response has been found beneficial against many chronic viral pathogens ( 5 , 54 , 83 86 ). Induction of T cells with multiple antigen-specificities correlates with advanced killing capacity for control of HCV or even complete eradication during primary infection with HCV and superior protection upon reinfection ( 80 , 86 , 87 ). Analysis of CD8 + T cell responses in untreated HIV-infected individuals showed that an increasing breadth of Gag-specific responses is associated with decreased viremia ( 88 ).…”
Section: The Breadth Of the Induced T Cell Response Impacts On Protecmentioning
confidence: 99%